Comprehensive analysis and validation of the prognostic significance of cuproptosis-related genes in rectal adenocarcinoma - Li, Tianhao; Gao, Xinyu; Zhang, Shuocun; Jing, Haoren; Pu, Zhicheng; Zhang, Xipeng; Zhang, Mingqing (Frontiers in Cell and Developmental Biology, 2025)
BackgroundRectal adenocarcinoma has a high incidence and suboptimal therapeutic outcomes. Notably, reliable prognostic biomarkers are currently lacking. Cuproptosis is a newly identified regulated cell death mechanism, and its molecular pathways and implications for rectal adenocarcinoma remain poorly understood. However, compared with colon adenocarcinoma, multi-omics studies of cuproptosis-related genes for rectal adenocarcinoma remain blank.MethodsThis study is the first to construct a cuproptosis-related genes prognostic prediction model for rectal adenocarcinoma by integrating genomics, transcriptomics, and clinical data. Transcriptomic data from the Gene Expression Omnibus and The Cancer Genome Atlas databases were analyzed. Cuproptosis-related genes were curated from prior literature and FerrDb V2. Consensus clustering was employed to identify molecular subtypes based on cuproptosis-related genes expression profiles. Subsequently, functional enrichment and survival analyses were conducted across subtypes. Following univariate Cox regression, LASSO regression, and multivariate analyses, four pivotal cuproptosis-related genes (PPAT, NHP2, INHBB, and MSMP) were selected to construct a prognostic risk model. The associations between risk scores, tumor microenvironment, immune cell infiltration, and drug sensitivity were further investigated.ResultsA total of 30 cuproptosis-related genes were screened, including 16 upregulated and 14 downregulated in rectal adenocarcinoma. These genes were enriched in pathways related to DNA/RNA metabolism, MAPK signaling, and calcium homeostasis. The LASSO regression risk model and nomogram demonstrated robust predictive accuracy for survival outcomes. Notably, cuproptosis-related genes were significantly correlated with immune cell infiltration and checkpoint gene expression, suggesting their dual role in tumor progression and immunomodulation.ConclusionThe prognostic system based on cuproptosis-related genes constructed in this study not only enhances the accuracy of survival prediction for rectal adenocarcinoma patients, revealing the potential role of cuproptosis in the tumor microenvironment and immune regulation, but also provides a new perspective for risk stratification and the selection of personalized treatment strategies, paving the way for precise oncology approaches in rectal adenocarcinoma.